Jean-Baptiste Say and the Classical Canon in Economics - Hollander, Samuel (Routledge Studies in the History of Economics, 2005)
This book explores the perceived paradigmatic conflict within British classical economics between the so called 'Ricardo School' and the contemporary French Economics of Jean-Baptiste Say. Samuel Hollander provides the reader with extensive evidence, utilizing all editions of Say's main texts and his lesser-known writings in order to demonstrate his adherence to much of Ricardian theory. This intriguing book focuses on selected doctorinal issues and surrounding debates, and will interest all serious historians of economic thought, finding a place on the bookshelves of many economists across the world.